Case series of vulvar intraepithelial neoplasia treated with imiquimod - Val, Isabel CC; Aidé, Susana; Gatto, Anna; Camacho, Camila; Vasconcellos, Jaqueline; Vicentini, Maria Fernanda; Val, Renata do; Val, Camila do; Bravo, Renato; Almeida, Gutemberg; et al. (Brazilian Journal of Sexually Transmitted Diseases, 2022)
The term vulvar intraepithelial neoplasia (VIN) includes the precursor lesions of vulvar cancer, being divided into squamous VIN and non-squamous VIN. The squamous VIN refers to the usual type VIN, which is related to HPV infection, multicentricity of lesions, sexual activity and smoking being more frequently observed in young woman. The VIN differentiated type, which is related to vulvar dermatoses, such as lichen sclerosus, is not associated with HPV-induced infection or sexual behavior and affects older patients. Thenon-squamous VIN is related to Paget’s disease and melanoma “in situ”. The standard VIN’s treatment is a surgical wide excision of the lesion with a safety margin. This study aims to test the use of imiquimod 5% cream in the treatment of usual type VIN isolated, and/or associated with surgical procedure. The imiquimod is already successfully used in the treatment of genital condylomatous lesions. Moreover, it has been shown to be effective in usual type VIN lesions.